Application of KNO3 and coconut water on papaya seed viability test (Carica papaya L) - dio tirta ardi; Haryati Haryati; Jonatan Ginting (Jurnal Agroekoteknologi, 2018)
Papaya is a dicotil plant that can only be developed with seed required, seed quality supported best production in field. For obtained good quality seed and increased production can be done several alternatives including by providing seed dormancy breaking KNO3 and coconut water. This research was conducted in Seed Technology Laboratory Agriculture Faculty University of Sumatera Utara, Medan from April to Mei 2016. This research used factorial randomized complete design with two factors. The first factor was concentration of KNO3 M0 (0%); M1 (2.5%); M2 (5%); M3 (7.5%) and the second factor is concentration of coconut water N0 (0%); N1 (25%); N2 (50%); N3 (75%); N4 (100%).Variabel observed was germination test (normal seedling, abnormal seedling, seed that have not grown),germination rate, vigor index, seedling fresh weight, and seedling dry weight. The result of this research showed that consentration of KNO3 were significantly increase to, normal seedling, vigor index, seedling fresh weight, seedling dry weight, and significantly decrease the seeds that have not grown. Concentration of coconut water were significantly increase to germination rate,vigor index, and seedling dry weight. Interaction of concentration of KNO3 and concentration of coconut water were not significantly effect to all parameters.